Beyond the scoreboard: coaches' UV-related skin cancer knowledge in outdoor sports - Schneider, Sven; Parsons, Zoe A.; Leer, Sophie (Journal of the European Academy of Dermatology and Venereology, 2025)
Background The global rise in UV radiation is widely recognized as one of the most relevant health impacts of climate change. Consequently, the prevalence of skin cancer is experiencing a significant increase, with outdoor athletes being identified as a particularly vulnerable population group. Objectives This study aims to investigate the extent of UV-specific skin cancer knowledge among coaches in outdoor sports and to examine potential variations in this knowledge between different sports, coach- and club-specific factors. Methods This nationwide representative study was conducted among outdoor sports coaches from the 10 largest outdoor sports associations in Germany. Their knowledge of the risks associated with UV radiation and prevention measures were evaluated using the Skin Cancer and Sun Knowledge Scale (SCSK Scale). Results Out of 1200 participating trainers, the UV-specific skin cancer knowledge score averaged 17.76 (±2.98) on a scale ranging from 0 to 25. The true-false statements ‘A tan is a sign that the skin is damaged’ (true) and ‘When using sunscreen, you can tan without any negative effects’ (false) were most frequently answered incorrectly. Only 16% of participants correctly identified basal cell carcinoma as the most prevalent form of skin cancer. Differences in UV-specific skin cancer knowledge were evident across different sports, with football and tennis coaches showing the major knowledge deficits. Conversely, trainers in skiing, swimming and mountain sports demonstrated the highest levels of knowledge. Significant deficiencies in knowledge were particularly notable among male trainers, as well as those from the youngest and the oldest age group, with limited training experience and who primarily worked with children and adolescents in small clubs on a regular basis. Conclusions Serious knowledge deficiencies are evident among German outdoor sports coaches. The study results emphasize the necessity for enhanced coach education and the implementation of evaluated concepts for climate adaptation in sports.